A new species of Aegus Macleay, 1819 (Coleoptera: Lucanidae: Lucaninae: Aegini) from Thailand with checklist of the genus species from the country - Pathomwattananurak, Wuttipon; Jiaranaisakul, Kawin (Zootaxa, 2024)
In this study, Aegus occidentalis Pathomwattananurak & Jiaranaisakul, new species is described from Tenasserim Range, western Thailand. Its habitus and genitalia are illustrated and compared with its closest relatives for both sexes. A checklist of the species of Aegus Macleay, 1819 (Coleoptera: Lucanidae: Lucaninae: Aegini) from Thailand is provided, which includes three new country records: Aegus babai Nagai, 1994, A. insignis Nagel, 1941 and A. laticollis Arrow, 1943. Additionally, a new junior synonym, Aegus chelifer Macleay, 1819 = Aegus chelifer crassodontus Bomans, 1992 new synonym, is proposed. Distribution maps of Aegus species in Thailand are also provided.